Formation of National Teams Taking into Account the Factors of Football Players' Club Migration - Eduard Sobol; Andrii Svatyev; Igor Doroshenko; Svitlana Kokareva; Nataliya Korzh; Eduard Doroshenko (OVS LLC, 2021)
Purpose. To determine the parameters of club migration of highly skilled legionary footballers when forming national teams for participation in official international competitions. Materials and methods. Population: 496 highly skilled football players ‒ participants of the 2022 World Cup group stage qualifiers. Results. The winning national teams with high UEFA coefficients have a smaller percentage of legionnaires than the group of winning teams with lower UEFA coefficients: 45.05% (coefficient 3.8) and 85.94% (coefficient 14.8), respectively. The indicators of dual citizenship have no significant impact on the formation of national teams, although the national teams of Wales, Turkey, and Scotland showed rather high values ‒ 9 (32.14%), 7 (28.00%), and 5 (20.00 %) of football players, respectively. Legionary footballers from the top six European leagues (England, Spain, Italy, Germany, France, Portugal) account for 87.50% of the total number of legionnaires who participated in the 2022 World Cup group stage qualifiers. Conclusions. Migration processes have an impact on the development of football at various levels of functioning: children and youth, reserve, student, amateur, semi-professional, and professional. Club migration, which is typical of highly skilled legionary footballers, has an indirect impact on the formation of national teams.